2019
DOI: 10.21608/ejcm.2019.43366
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Self-Esteem among School Adolescent Students, Alexandria City, Egypt

Abstract: Background:Obesity and low self-esteem are prevalent disorders among adolescents. Tackling this relationship may introduce effective intervention that promotes healthy adolescence. Objectives: to measure the prevalence of overweight and obesity and identify its relation with self-esteem among school adolescents. Method: A cross sectional study was carried out on 533 adolescents selected by multistage cluster sample.The students completed a structured questionnaire on dietary habits, physical activity and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Adolescence, a very important stage of human growth and development, is characterized by dynamic physical growth and maturation of secondary sexual characteristics [ 1 ]. It was declared by WHO (2022) in World Obesity Day 2022 that 340 million adolescents and 39 million children are obese worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence, a very important stage of human growth and development, is characterized by dynamic physical growth and maturation of secondary sexual characteristics [ 1 ]. It was declared by WHO (2022) in World Obesity Day 2022 that 340 million adolescents and 39 million children are obese worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that self-image is negatively connected obesity, inevitably results in low self-esteem (Dale et al, 2019), Study in Egypt revealed overweight and obesity affect more than a quarter of young people. Adolescents who are obese typically have lower self-image (Mohammed et al, 2019). When normal-weight and obese people were compared on their body images scores, it was found that the latter group, particularly women, had higher levels of body dissatisfaction (Weinberger et al, 2017).…”
Section: The Correlation Between Obesity and Self-image Of Teenage Gi...mentioning
confidence: 98%